Plant Tolerance Mechanisms to Soil Salinity Contribute to the Expansion of Agriculture and Livestock Production in Argentina - Taleisnik, Edith; Rodríguez, Andrés Alberto; Bustos, Dolores Angela; Luna, Dario Fernando (Springer, 2021)
This chapter addresses salt tolerance mechanisms in crops and woody species cultivated in Argentina, highlighting the contribution of local research to these topics. Work on forages and woody species represents approximately half of this research that has been published by Argentine authors in international journals. Basic research on plant salinity mounts to only 12% of the total, indicating that it still does not attract sufficient consideration among researchers. Among forage plants, attention in this chapter is focused on Rhodes grass (Chloris gayana Kunth), while in woody perennials, salt tolerance mechanisms in Prosopis, which have been extensively investigated locally, are reported. Despite the importance of soybean in Argentine economy, as well as that of other crops such as maize, wheat, sunflower, relatively little research attention has been paid to salinity issues in these major field crops. This situation may reflect the fact that they are mostly cultivated in non-saline soils.